Nilai Gizi dan Penggunaan Bahan Tambahan Pangan Berbahaya pada Siomay yang dijual di Kampus USU Medan - Zulhaida Lubis; Jumirah Jumirah; Atikah Ulfa; Ros Idah Rohna Berutu (Jurnal Gizi dan Kuliner (Journal of Nutrition and Culinary), 2021)
Dumplings is a street food favored by the community, usually sold on the roadside or school environment, including at the campus of Universitas Sumatera Utara (USU) Medan. On the other hand, the widespread issue of the use of various food additives that are prohibited, demands the importance of information on the safety of various snacks. This study aims to determine the nutrient content of dumplings and the content of food additives that are prohibited from serving dumplings sold around the campus of USU Medan. This type of research is an analytic survey, conducted around the campus of USU Medan in July 2018. The subject of the study was dumplings taken from 21 traders, carried out by buying one serving of dumplings from each trader. The analysis of food additives consisting of formalin and borax in the tofu and  dumplings and Rhodamin B in the sauce, and was analysed at the Laboratory of Faculty of Public Health USU. WhileThe nutritional content is calculated based on the ingredients for making dumplings. The results showed that the energy content of serving dumplings ranged from 374.8-613 kcal, protein 18.5-34.9 g, fat 23.9-40.9 g, carbohydrates 21.9-61.1 g, fiber 3 ,1-6.1 g, vitamin A 11-134.4 µg, phosphorus 200.3-445.1 mg, calcium 57.3-208.7 mg and iron 3-8.3 mg. Found one serving of dumplings containing formalin in the tofu used.  While the results of borax and rhodamine B were not found in all samples of dumplings. It can be concluded that the dumplings sold at the USU campus and its surroundings are considered safe, except that there is still one trader who uses formalinated tofu. Thus, it is necessary to approach dumplings sellers who are formalized in order to replace the source of tofu used.